2008
DOI: 10.2478/s11756-008-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Some epidemiological and epizootiological aspects of Lyme borreliosis in Slovakia with the emphasis on the problems of serological diagnostics

Abstract: The paper analyses the results of serological examinations of domestic, farm and free-living animals from different regions of Slovakia, Southern Moravia, Southern Bohemia and Southern Poland using ELISA, indirect hemagglutination assay (IHA) and Western blot (WB). In Slovakia, significantly higher seroprevalence was recorded in dogs (33.5%) than in horses (26.5%), cattle (22.5%), sheep (16.6%) and rodents (17.8%) by using a mixture of Borrelia garinii, B. afzelii, B. burgdorferi sensu stricto (s.s.) antigens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In accordance with the literature, no relationship has been established between seroreactivity to B. burgdorferi s.l. and gender or age (Delgado and Cármenes 1995;Š tefan cíková et al 2008;Couto et al 2010;Kiss et al 2011). The lack of correlation may be a consequence of the limited persistence of anti-B.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the literature, no relationship has been established between seroreactivity to B. burgdorferi s.l. and gender or age (Delgado and Cármenes 1995;Š tefan cíková et al 2008;Couto et al 2010;Kiss et al 2011). The lack of correlation may be a consequence of the limited persistence of anti-B.…”
Section: Discussionmentioning
confidence: 99%
“…The highest seroprevalence in asymptomatic sheep was determined in France (56.5%) ( 73 ). The only study containing data on goats reported a 17.2% seroprevalence rate in this species in Slovakia ( 74 ). Direct pathogen detection, e.g., by PCR, was not reported for ruminants in the considered studies.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that cross-reactivity with other pathogens, e.g., Leptospira spp. ( 74 ), may have been an issue, especially in older and in non-canine studies.…”
Section: Discussionmentioning
confidence: 99%
“…The highest seroprevalence in asymptomatic sheep was determined in France (56.5%) (73). The only study containing data on goats reported a 17.2% seroprevalence rate in this species in Slovakia (74). Direct pathogen detection, e.g., by PCR, was not reported for ruminants in the considered studies.…”
Section: Ruminantsmentioning
confidence: 86%
“…This indicates that crossreactivity with other pathogens, e.g., Leptospira spp. (74), may have been an issue, especially in older and in non-canine studies.…”
Section: Discussionmentioning
confidence: 99%